Protozapotecia acaxetlensis and Protozapotecia oyametlensis, two new earthworm species (Crassiclitellata: Acanthodrilidae) from Mexican central mountains - Cervantes, Gabriela; Fragoso, Carlos (Zootaxa, 2018)
Two earthworm species from central Mexico are described: Protozapotecia acaxetlensis sp. nov. and Protozapotecia oya-metlensis sp. nov. Delimitation of species was supported by morphological and molecular evidence. The two new species differ from the other species of Protozapotecia by the position of the prostates in segments 18 and 20. This morphological characteristic relates them to the genus Diplocardia, from which they differ by the presence of two gizzards separated by a muscular septum (Protozapotecia), instead of two gizzards fused as one, separated by a thin membranous septum in intersegment 5/6 (Diplocardia).